Compensatory Shift of Subcallosal Area and Paraterminal Gyrus White Matter Parameters on DTI in Patients with Alzheimer Disease - Kuchtova, Barbora; Wurst, Zdenek; Mrzilkova, Jana; Ibrahim, Ibrahim; Tintera, Jaroslav; Bartos, Ales; Musil, Vladimir; Kieslich, Karel; Zach, Petr (Current Alzheimer Research, 2018)
Objective: Alzheimer disease is traditionally conceptualized as a disease of brain gray matter, however, studies with diffusion tensor imaging have demonstrated that Alzheimer disease also involves alterations in white matter integrity. We measured number of tracts, tracts length, tract volume, quantitative anisotropy and general fractional anisotropy of neuronal tracts in subcallosal area, paraterminal gyrus and fornix in patients with Alzheimer disease and healthy age-matched controls. Our hypothesis was that patients with Alzheimer disease should exhibit decrease in the integrity of these white matter structures that are crucial for semantic memory function. Methods: For our study were selected 24 patients with confirmed Alzheimer disease diagnosis and 24 healthy controls (AD center, Department of Neurology, Charles University, Prague, Czech Republic). Statistically significant differences between the patients with Alzheimer disease and the control group were found both on the left and right fornices but only concerning the tract numbers and tract length. The subcallosal area and paraterminal gyrus showed statistically significant differences between the patients with Alzheimer disease and the control group, but only on the left side and only associated with the tract volume and quantitative anisotropy. Conclusion: Our explanation for these findings lies in the severe hippocampal atrophy (and subsequent loss of function) with compensatory hypertrophy of the subcallosal area and paraterminal gyrus neuronal fibers that occurs in Alzheimer's disease, as an adaptation to the loss of projection from the hippocampal formation via fornix.
Keywords: Alzheimer' s disease